La atención y su incidencia en las conductas de base en los niños de 3-5 años del Centro de Desarrollo de la Niñez EC-420, de la comunidad Pulingui, parroquia San Andrés, cantón Guano, provincia de Chimborazo. año 2014-2015 - Gualancañay Pacheco, Rubí Alicia (2016)
This research was conducted at the Center for Child Development EC-420, being of great interest care and their impact on behavior base, child in preschool age are shortcomings in the uptake of the different activities, making and socially interact inappropriately with adults outside the family system and its peer group. According to the objectives set we different activities that will help develop basis behaviors through good care, In hypothesis testing it was determined that the care influences basis behavior on children 3 to 5 years identified the research method employed was inductive, deductive and analytical, to collect data, as technical the survey and observation was used, the type of research is descriptive, exploratory and documentary. After the diagnosis was clear that the highest percentage of children do not pay attention to the activities taking place in the classroom, a teaching guide for this was made "Meetings My Little Words" as a tool for teachers. At the conclusion of this research based behaviors with children on a regular basis in the classroom, children do not have this predisposition to carry out any activity which directly affects their behavior, also does not demonstrate the necessary interest and in disorder in the different activities. Recommending work on strengthening and development of attention of children for a better development of the various activities as this is a great tool for the development of behavior based on children 3-5 years- old of the Centre Childhood Development EC-420.